Body mass index and prognosis of breast cancer: An analysis by menstruation status when breast cancer diagnosis. Issue 26 (June 2018) - Sun, Li; Zhu, Yulan; Qian, Qi; Tang, Liming
Abstract: Objective: To examine whether obesity/overweight is a risk predictor for breast cancer recurrence and death by menopausal status in a retrospective study. Methods: We performed a retrospective analysis of 1017 breast cancer patients treated in our hospital from January 2004 to December 2012. Three groups were divided according to body mass index (BMI) when breast cancer diagnosis: normal weight, BMI < 25.0 kg/m 2 ; overweight, 25.0⩽BMI < 30.0 kg/m 2 ; and obesity, BMI≥30.0 kg/m 2 . The clinicopathological characteristics and clinical outcomes of patients within 5 years following breast cancer diagnosed were analyzed. Subgroup analyses of BMI on breast cancer prognosis were analyzed according to the menopausal status when breast cancer diagnosis. The Cox proportional hazards model was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Overweight and obesity groups were associated with larger size tumors, older age, increased proportion of postmenopausal patients and less patients choosing anthracycline and/or taxane regimen. The 5-year disease-free survival (DFS) and overall survival (OS) decreased in overweight and obese patients ( P  < .001), and both overweight and obesity were independent predictors for increased risks of breast cancer relapse and death ( P  < .001). When stratified by menopausal status, both overweight and obesity were associated with reduced 5-year DFS and OS in postmenopausal patients ( P  < .050), and multivariate analysis showed that the risk of relapse and breast cancer mortality in these 2 groups also increased ( P  < .050). Among premenopausal patients, the risks of relapse and death were significantly increased in obesity group rather than overweight group by multivariate analysis. Conclusion: Overweight and obesity might be independently associated with poorer prognosis for breast cancer patients, and the effects of overweight on the breast cancer prognosis seem to be related to menopausal status.